Using CATIA V5 - Karam, Fred (Thomson/Delmar Learning, 2004)
This professional how-to guide introduces CATIA V5 users to all of the information they need for successful feature-based design and 3D computer modeling. Fast-paced yet comprehensive coverage includes customizing toolbars, developing relationships between 2D geometrical elements, feature-based modeling do's and dont's, creating assemblies models, interacting with 3D solid model features, and more! Issues of data exchange and interoperability between V4 and V5 are also addressed, making this manual a must for every serious CATIA user